Additive metal printing machine tool - Takács, György; Kiss, Lotár László (Design of Machines and Structures, 2021)
The 3D printing, as a modern manufacturing method, is becoming more widespread and overrides the usual industry conventions. While it was mainly known in the production of plastic parts, nowadays metal-based versions are also becoming more widespread. Reputable machine tool manufacturers such as DMG Mori or GE compete with each other to create equipment for this technology for the industry, where there is a growing market for such machines. My article seeks to answer the question of where these tools have a place in the industry, whether they can be considered as machine tools, and decide that the procedures describing the construction of machine tools could be applied to them.